Petrological and Geochemical Study of Sundoro Volcano, Central Java, Indonesia: Temporal Variations in Differentiation and Source Processes during the Growth of an Individual Volcano - Wibowo, Haryo Edi; Nakagawa, Mitsuhiro; Kuritani, Takeshi; Furukawa, Ryuta; Prambada, Oktory; Harijoko, Agung (Oxford University Press, 2022)
Volcanic rocks of the Java sector of Sunda arc have a wide range of isotopic compositions that indicate significant addition of subjected sediment. What processes control these geochemical characteristics is a topic of long-standing debate. Here we report Sr-Nd-Pb radiogenic isotope ratios and geochemical data from stratigraphically well-constrained rocks of Sundoro volcano in central Java that represent the volcano's activity since 34 ka. The rocks range from basalt (51 wt SiO2) to andesite (63 wt SiO2) and are dominated by basaltic andesite. We divide them into magma types A, B and C, having low, medium and high 87Sr/86Sr and Pb isotopic ratios, respectively. According to various differentiation indices, the three magma types have separate, parallel 87Sr/86Sr, Ba/Zr and La/Yb trends and disparate Pb isotopic trends. The dominant process of intracrustal differentiation appears to be magma mixing, in which each of the three magma types represents the mixing of a distinct mafic end-member and a distinct felsic end-member. The distinct geochemical profiles of these magma types indicate that the three mafic end-members are genetically unrelated and that their differences may represent characteristics of their magma sources. On the basis of trace element ratios (Ba/Yb and La/Yb) and Sr-Nd-Pb isotopic compositions, we estimate that magma types A, B and C represent mantle wedge materials fluxed by ~1, ~1.5 and ~2 slab-derived materials containing 50, 55 and 65 sediment component, respectively, reflecting increasing proportions of sediments and increasing slab flux. Geochemical data from Merapi volcano, interpreted using the same approach, reveal a similar increase in the slab-derived flux to the magma source, raising the possibility that such short-lived variations in magma genesis, perhaps related to the subduction of bathymetric relief features, characterize the unusual magmatism beneath the volcanic front of the central Java sector of the Sunda arc. © 2022 The Author(s). Published by Oxford University Press. All rights reserved.